2009
DOI: 10.1021/ja907515s
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Rate Atomic Trajectories of RNA by Solid-State NMR Spectroscopy

Abstract: Many RNAs undergo large conformational changes in response to the binding of proteins and small molecules. However, when RNA functional dynamics occur in the ns-μs time scale they become invisible to traditional solution NMR relaxation methods. Residual dipolar couplings methods have revealed the presence of extensive ns-μs domain motions in HIV-1 TAR RNA, but this technique lacks information on the rates of motions. We have used solid-state deuterium NMR to quantitatively describe trajectories of key residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
101
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(116 citation statements)
references
References 38 publications
9
101
5
1
Order By: Relevance
“…To determine the transient structures with a lifetime of few micro-to-milliseconds, a method to measure RDCs of the transient states has been developed. 78 Paramagnetic relaxation enhancement 79 and the solid-state NMR 80,81 can be also utilized to characterize the transient structures of RNA. All the NMR experiments including the ones described in this review, and additional NMR parameters can complement each other to improve the temporal and spatial resolution of RNA behavior.…”
Section: Perspectivesmentioning
confidence: 99%
“…To determine the transient structures with a lifetime of few micro-to-milliseconds, a method to measure RDCs of the transient states has been developed. 78 Paramagnetic relaxation enhancement 79 and the solid-state NMR 80,81 can be also utilized to characterize the transient structures of RNA. All the NMR experiments including the ones described in this review, and additional NMR parameters can complement each other to improve the temporal and spatial resolution of RNA behavior.…”
Section: Perspectivesmentioning
confidence: 99%
“…In a subsequent study [167], detailed models of the dynamics of the three deuterated sites, on the ns-μs timescale, were derived from analysis of 2 H lineshapes and R 1 , R 1Q relaxation data. It was found that U23 and U25 (Fig.…”
Section: Nmr Studies Of the Dynamics Of Biomolecular Conformationamentioning
confidence: 99%
“…Solidstate 2 H NMR spectroscopy was used to describe motion of selected residues in TAR RNA from HIV-1 during protein recognition. [16] NH···N hydrogen bonds in (CUG) 97 RNA were detected by 15 N MAS NMR spectroscopy. [17] 1 H correlation was combined with high-resolution spectral dimensions in NHHN, CHHC, and NHHC experiments.…”
mentioning
confidence: 99%